From Punishment to Transformation: A Phenomenological Study on Post-Traumatic Growth in Former Prisoners - Kirana, Rhein Sasi; Asad, Amiroh Untsal; Indrijati, Herdina (Psympathic : Jurnal Ilmiah Psikologi, 2025)
Trauma experienced after incarceration is a heavy burden for former prisoners during their reintegration into society. Apart from social stigma and economic difficulties, prisoners frequently face profound psychological pressure due to traumatic experiences during imprisonment. This study aimed to investigate the experience of PTG among former prisoners in Indonesia after their release. A phenomenological design was used and semi-structured interviews were conducted with 6 male former prisoners. Interpretative Phenomenological Analysis (IPA) was also used to analyze participant responses. Participants' perceptions of PTG showed five key themes, namely (1) self-understanding and personal development, (2) relationships with family and social networks, (3) spirituality and relationship with God, (4) coping strategies and mechanisms, and (5) a greater sense of meaning in life. The results corresponded to Tedeschi and Calhoun's theory and introduced an additional theme regarding coping strategies and mechanisms. In conclusion, the development and implementation of psychosocial interventions should be prioritized for former prisoners.